Influence of Aluminium and Autoclaving Temperature on the Properties of Autoclaved Aerated Concrete - Islam, Mohei Menul; Rashid, Muhammad Harunur; Muntasir, Md Aqib (Journal of Engineering Science, 2022)
Autoclaved aerated concrete (AAC) prepared by the mixing of ordinary Portland cement, lime powder, sand, aluminium powder and water. This study covers the variation of physical, mechanical and functional properties of autoclaved aerated concrete with autoclaving temperature and aluminium content and compared with that of normal weight cement mortar sample. In this work, two dosage of aluminium content of 0.4% and 0.8% of the dry weight of ordinary Portland cement and three different autoclaving temperature of 160oC, 180oC and 200oC were used. AAC sample with 0.8% aluminium and 160oC temperature had unit weight of 1490kg/m3 which was lowest among all samples including the control or normal weight cement blocks. Weight reduction of AAC sample was 31.53%. AAC sample with 0.4% aluminium and 200oC autoclaving temperature gave maximum compressive and tensile strength of 19.4MPa and 1.81MPa respectively which were close to that of normal weight concrete and strength of AAC increased with autoclaving temperature and decreased with aluminium content. In this research, the functional propertiesof AAC, absorption capacity was much higher than normal weight concrete and this capacity was increased with aluminium content and with decreasing autoclaving temperature and unit weight of AAC. For AAC with 0.8% aluminium and 160oC temperature gave maximum water absorption capacity (=9.93%). Again, surface absorption rate was higher for first 12hours and with time it would be constant because of its saturated position. Journal of Engineering Science 12(3), 2021, 11-17